Preparatory actions and indicators for their assessment in competitive fights of highly qualified karatekas in the olympic weight category up to 67 kg - Orlov, Y. L.; Tian, Z.; Ryzhkova, L. G.; Orlova, A. Y. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the versatility, effectiveness and success of preparatory actions used in competitive fights by highly qualified karatekas for the successful implementation of offensive and defensive actions.